Global talent management and higher education governance : the Singapore experience in a comparative perspective - Liu, Hong (Edward Elgar Publishing, 2021)
Using Singapore as a case study, this chapter is concerned with the roles of global talent management in the higher education and research sectors and how it has contributed to a nation's socio-economic development. The first section of this chapter reviews the existing literature on global talent management and its limitations in understanding non-Western experiences. The second section examines the Singapore government's policy on higher education and on how the twin focuses on talent development – including both domestic and global talent management – and economic development have been skilfully incorporated in the country's transformation since its independence in 1965. It gives special attention to former Prime Minister Lee Kuan Yew's views on the critical role of talent in political and economic development and the effective implementation of talent strategies. The third section of this chapter zooms in on the development of Nanyang Technological University in Singapore over the past 27 years since its founding, especially over the past decade, to highlight the importance of (global) talent management behind its dynamic rise in the international higher education and research scene. The concluding section considers Singapore's experience in a comparative perspective and offers some preliminary suggestions for future research directions with respect to global talent management and higher education governance.